TRANSITIONAL JUSTICE: : ARE TRUTH AND RECONCILIATION COMMISSIONS WORTH IT? (Revista dos Estudantes de Direito da Universidade de Brasília, 2012)
Truth and reconciliation commissions are becoming an  increasingly popular method used by the international community towards  promoting transitional justice.  However, many victims of human rights  violations resort to further means of pursuing justice even after a truth and  reconciliation commission has been engaged, which brings the question  of whether truth and reconciliation commissions are worth the time and  money they require.  Incomplete justice and tokenism are among the reasons  that it can be argued that a truth and reconciliation commission is not an  efective alternative in facilitating reparations after human rights atrocities  have occurred.  Te following analysis explores this question and eventually  identifes valuable transitional justice outcomes that are unique to truth and  reconciliation commissions.